(untitled) (Nigerian Journal of Technology, 2019)
Particle size distribution and void ratio of a soil are considered as the direct information that can be used in a relatively easy manner for hydraulic conductivity estimation. Estimation of hydraulic conductivity from particle size distribution can be used to check permeability values obtained from other methods. Therefore, this paper attempts to relate the particle size distribution to hydraulic conductivity. The study was carried out on 24 soil samples which were collected from the embankment of an earth reservoir and subgrade at the toe. The investigation was carried out in accordance with the standard procedure given in BS1377. A series of hydraulic conductivity tests were carried out on optimum moisture content (OMC) compacted soil samples using the falling head method. The mean sizes of particles in each sample from particle size distribution curves were determined and used to generate regression models for the flow. Linear, exponential, polynomial and logarithmic models were used to test the validity; however, the best was adopted for this study. The findings of this study show that there is variability in the particle sizes of the soil material which in turn results to variation in the hydraulic conductivity. The hydraulic conductivity was found to increase with an increase in mean particle size. The relationship between mean particle size and hydraulic conductivity yielded coefficients of determination (R2) of stronger correlation when the plastic and non-plastic samples were separately analyzed. However, all values of R2 (0.9949, 0.9968 and 0.8918 for samples 1 to 16, 17 to 24 and 1 to 24 respectively) can be considered satisfactory. In addition, generalized models for the flow were generated for the plastic, non-plastic and the combined samples. The generated models can be used to predict the hydraulic conductivity of different soil samples. http://dx.doi.org/10.4314/njt.v38i3.6